2019
DOI: 10.1007/s11269-019-02399-1
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Streamflow Forecasting Using the Feature-Enhanced Regression Model

Abstract: Reservoir inflow forecasting is extremely important for the management of a reservoir. In practice, accurate forecasting depends on the feature learning performance. To better address this issue, this paper proposed a feature-enhanced regression model (FER), which combined stack autoencoder (SAE) with long short-term memory (LSTM). This model had two constituents: (1) The SAE was constructed to learn a representation as close as possible to the original inputs. Through deep learning, the enhanced feature could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…The results show that performance criteria used in the process of model calibration and the length of the warm-up period had a larger effect on the model results than selection of the equation used for calculating the mean daily air temperature (Section 3.2). Similar results would be expected in the case of shortening or extending the length of the calibration period [40]. However, some studies have indicated that shorter periods could be sufficient for efficient model calibration [41,42].…”
Section: Impact Of the Measurements Error On The Rainfall-runoff Modelling Resultssupporting
confidence: 78%
“…The results show that performance criteria used in the process of model calibration and the length of the warm-up period had a larger effect on the model results than selection of the equation used for calculating the mean daily air temperature (Section 3.2). Similar results would be expected in the case of shortening or extending the length of the calibration period [40]. However, some studies have indicated that shorter periods could be sufficient for efficient model calibration [41,42].…”
Section: Impact Of the Measurements Error On The Rainfall-runoff Modelling Resultssupporting
confidence: 78%
“…Yang and Wang [ 15 ] provided the employment situation of graduates of civil aviation aircraft; due to its complex and irregular curve shape, it is laborious for the existing single model to realize the ideal forecast effect. To this end, Xu et al [ 16 ] conceived a hybrid method based on SSA and SVR. The method first selects the fault feature components from the original data and then models and forecasts them separately, and obtains better experimental results than a single model.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, for the Ljubljanica river, such water retention is even increasing the peak discharge, which can be attributed to the karst characteristics of the Ljubljanica river catchment [53,55,69] and outflow from the reservoirs that shifts the peak discharge for a few hours as shown in Section 2.4. More specifically, several natural karst poljes (e.g., lake Cerknica or Planinsko polje) are located in the Ljubljanica river catchment that act as extensive natural retention reservoirs leading to a lagged (i.e., slower) response of the Ljubljanica river catchment compared to more torrential rivers such as Sava or Savinja [70]. A similar conclusion can be seen if one would construct some dry retention reservoirs in the Gradaščica river catchment (Tables 6 and 7).…”
Section: Sensitivity Analysismentioning
confidence: 53%